Review of Cultural Preservation Theory in Cultural Heritage Sustainability Case Study of Peliatan Ubud Palace - Salain, Nyoman Ratih Prajnyani; Putra , I Dewa Gede Agung Diasana; Dwijendra , Ngakan Ketut Acwin; Susanta, I Nyoman (Universitas Ibn Khaldun Bogor, 2025)
This research aims to review cultural preservation theory in the context of cultural heritage sustainability with a case study of Peliatan Palace in Ubud, Bali. The intended conservation theory is a theory by Sendjaja which consists of Culture Experience and Culture Knowledge. Peliatan Palace is one of the cultural heritage sites in Bali which is still preserved today and has high historical and cultural value. This research uses qualitative methods with a case study approach to reveal how cultural preservation is carried out at Peliatan Palace and the factors that influence the sustainability of this cultural heritage. The research results show that cultural preservation at Peliatan Palace is carried out through various efforts, including maintaining the traditional architecture of the castle, carrying out traditional ceremonies, and active involvement of local communities in cultural activities. Internal factors such as the commitment of the Palace family and external factors such as government support and tourism play an important role in maintaining cultural preservation at Peliatan Palace. Apart from that, adapting to current developments without eliminating traditional values ​​is also the key to maintaining the cultural heritage of this castle. This research concludes that cultural preservation at Peliatan Palace is not only important for maintaining local cultural identity but also having a positive impact on community welfare and the promotion of Balinese culture on the international stage. Sustainable and adaptive preservation efforts to changing times are needed to ensure that future generations can enjoy this cultural heritage.